RICE (ORYZA SATIVA L.) ANDROGENESIS IN VITRO (Experimental biology, 2024)
Rice (Oryza sativa L.) is a cereal crop cultivated mainly in tropical and even some subtropical countries and provides food for more than half of the world's population. Nowadays, haploid biotechnology (gynogenesis and androgenesis) is used in breeding practice as one of the tools to improve rice, preferably in vitro androgenesis. The method of in vitro cultivation of male gametophyte is one of the promising biotechnological approaches in crop breeding research, including rice. This method is based on the biological phenomenon of androgenesis - formation of haploid regenerant plant from anther and microspore cells, whose development switches from gametophytic to sporophytic pathway. However, the wide application of these technologies is limited by the existing two problems associated with the genotype-dependence of plant regeneration and formation of albino plants in many cases in in vitro male gametophyte culture of rice. The need to eliminate these restrictions has been and remains. This requires continued research in this direction to develop and optimize the technology of cultivation, pre-treatment of anthers and components of the nutrient medium, universal for all rice genotypes. This review considers a number of factors that affect the efficiency of rice androgenesis in vitro.
Keywords: Rice (Oryza sativa L.), androgenesis in vitro, anthers culture, isolated microspores culture, limiting factors.